PENAMBAHAN TEPUNG TAPIOKA DENGAN LEVEL YANG BERBEDA TERHADAP MUTU ORGANOLEPTIK BAKSO DAGING KAMBING (Addition of tapioca flour with different levels on the organoleptic quality of goat meat balls) - Tondang, Santi Bestari; Berutu, Karina M.; Sihombing, Juli M. (JURNAL NUKLEUS PETERNAKAN, 2024)
Goat meat has characteristics such as a darker color, smoother, softer, more pungent odor, tough, chewy fat, and a yellowish whitish color. There is a need for meat processing to extend the shelf life of meat and increase its economic value while maintaining its nutritional content. Making goat meat meatballs is an effort to promote the use of goat meat in processed meat products, especially meatballs. The aim of the research was to determine the effect of adding tapioca flour at different levels on the organoleptic properties of mutton meatballs. Research parameters include sensory assessments by a panel of judges which include aspects of color, texture, taste and elasticity of the meatballs. This research used the Kruskal-Wallis Method with four treatments: T1(5%), T2(15%), T3(25%), and T4(35%), and evaluated the color, texture, taste and elasticity of the product. meatball. The results of the research showed that there was a real influence of differences in tapioca flour levels on the texture of goat meatballs, while color, taste and elasticity did not show a real influence. The addition of tapioca flour as a filler at a level of 15% (T2) produces the most preferred texture for goat meatballs. The results of the research show that the addition of tapioca flour at different levels produces an impact that is in accordance with the panelists' preferences for the color, taste and elasticity of the meatballs. However, there is a striking difference in its effect on the texture of the meatballs.